Thermodynamic studies of hydrated metal oxide precipitate for the removal of fluoride from water - Paudyal, Hari; Pangeni, Bimala; Ghimire, Kedar Nath; Inoue, Katsutoshi (Scientific World, 2022)
Hydrated tri metal oxide (HTMO) precipitate is investigated using a mixed solution containing cerium, aluminum, and titanium by precipitation for fluoride ion removal from water.PZC for the investigated HTMO precipitate is determined to be 6.5 from pH drift method. Fluoride adsorption by HTMO precipitate is pH dependent, with adsorption rates of more than 98 percent occurring at pH 2.3 to 6.7. The highest solid phase distribution of fluoride is observed at pH around 6. Fluoride adsorption onto HTMO precipitate increased with temperature, implying that the adsorption reaction is endothermic, as evidenced by the positive value of ∆H⁰ calculated from the thermodynamic calculations. The spontaneous process is indicated by a negative ∆G⁰ value for alltemperatures. The fluoride adsorption rate onto this adsorbent is rapid, and equilibrium is reached in less than four hours. An alkali (NaOH) solution effectively desorbed fluoride from a fluoride-loaded HTMO precipitate. As a result, the HTMO precipitate studied in this work is expected to be a viable as fluoride-removing material from water.